Severe Esophageal Stricture Post Accidental Corrosive Substance Ingestion: A Case Report of Balloon Endoscopic Dilation - Leen Jamel Doya; Maria Naamah; Hanin Ahmed Mansour; Ali Ibrahim; Ammar Omran (Case Reports in Pediatrics)
Corrosive substance ingestion is a very serious home accident, mostly common in developing countries. It frequently causes esophageal burns in the acute stage and esophageal stricture, stenosis, and even cancer in the chronic stage. Severe cases of caustic esophagitis may require esophageal replacement. We describe a case of balloon endoscopy dilation in a two-year-old girl with a severe stricture of the esophagus resulting from accidental ingestion of a corrosive substance (strong alkaline liquid) which helped the patient preserve the esophagus and prevent esophageal replacement. We describe the clinical complication and development during the treatment.